Tafqīq Ṭarīqah Ramy Kurah al- Ṡalj (Snowball Throwing) fī Tanmiyah Mahārāh al-Qirā’ah Ṭullāb Madrasah Islāmiyyah Mutawassitah Ḥukumiyyah 1 Bukittinggi - Anisa Zakiah; Wira Wahyuni (Qawa’id: Jurnal Bahasa dan Sastra Arab, 2025)
This study aims to examine how the Snowball Throwing method is applied in teaching at Madrasah Tsanawiyah State 1 Bukittinggi. The background of this research is based on the need to improve students’ reading comprehension and increase their active participation, as students often find reading activities uninteresting. The research method used by the researcher is descriptive-analytical research, and the data collection tools used in this study include observation, interviews, and documentation. Observations and interviews were conducted during the teaching and learning process to directly observe students’ interactions during the implementation of the Snowball Throwing method. Interviews were conducted with the teacher and students. Documentation was used to collect additional data such as daily notes, teaching materials, and students’ relevant work. The research results indicate that the Snowball Throwing method is able to improve students’ reading comprehension and increase their active participation. Students became more motivated and engaged in the learning process. This method also helps create an effective and enjoyable learning environment. Based on these results, the Snowball Throwing method can be considered as a viable alternative for teaching reading in schools.